2006
DOI: 10.21608/jesaun.2006.110472
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Woven Fabric Reinforced Epoxy Composites Under Bending and Compressive Loads

Abstract: The mechanical behavior of epoxy reinforced by three different types of woven fibers was studied under compressive and bending loads. The reinforcements used were: woven glass fibers (volume fractions: 9.2%, 18.4%, 27.6%, and 36.8%), woven carbon fibers, and woven hybrid (carbon/glass) fibers at 36.8 vol.%, each. The composites were manufactured using the hand lay-up technique. Pure (unreinforced) epoxy specimens were tested as a reference material. The fracture behavior of the investigated specimens was studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…The Kevlar/epoxy composite has the lowest bending stress and stiffness but the highest strain, evidencing the ductile nature of the fibers that are classified as high-elongation fibers [27,28]. Finally, the results described above are supported by several studies that evoked similar conclusions [12][13][14][23][24][25][26][27][28] and are a consequence of the different damage mechanisms.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…The Kevlar/epoxy composite has the lowest bending stress and stiffness but the highest strain, evidencing the ductile nature of the fibers that are classified as high-elongation fibers [27,28]. Finally, the results described above are supported by several studies that evoked similar conclusions [12][13][14][23][24][25][26][27][28] and are a consequence of the different damage mechanisms.…”
Section: Resultssupporting
confidence: 55%
“…Wonderly et al [11] also reported that the ratio of compressive strength over tensile strength is different for carbon and glass fiber composites, with values around 0.34 and 0.73, respectively. In fact, Santos et al [12] and Ghafaar et al [13] reported that full-carbon composites have the maximum bending stress and stiffness, while fullglass fiber laminates have the lowest value, reaching a difference in bending strength of about four times [14]. Therefore, by adding carbon fibers on the tensile side of glass fiber composites, the flexural strength will increase, while on the compression side the strength will decrease [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The glass fiber composites exhibited maximum fracture toughness was 131.90 MPa.mm 1/2 . Abdel Ghafaar et al [17] established three different types of woven fibers in the epoxy resin and prepared by hand lay-up method to evaluate the mechanical properties under the effect of bending loads and observed that the maximum values of the flexural strength and modulus at CFRP compared to the hybrid composites and GFRP were 360 MPa, 17.11 MPa, respectively. In addition, Chinta et al [18] carried out the single edge notch bending (SENB) to study the mode-I fracture toughness for non-hybrid woven carbon/epoxy (C20), and hybrid carbon core composite (G5C10G5), experimentally and finite element modeling (ANSYS).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of these laminates were investigated through quasi-static tensile and 3-point bending tests, short-beam shear tests, and mode I interlaminar fracture toughness tests. The bending load–displacement curves of all laminates ( Figure 3 A) show an initial linear region, but for the neat EP-CFu laminate, the load drops to zero immediately after the maximum value, indicating a sudden and catastrophic failure, which was reported as a sign of good interlaminar adhesion [ 52 , 53 ]. On the other hand, MCs change the failure mode and make the load decreasing stepwise after the maximum, indicating energy dissipation also during damage propagation.…”
Section: Case Study: Epoxy/carbon Laminates Containing Paraffin Microcapsulesmentioning
confidence: 99%